Catheter body-surface fixation after transurethral prostate resection: A low-value nursing practice as evidenced in a randomized controlled trial - Yanan Zhu; Qian Wang; Huiying Jia; Gaiyun Zhao; Yunpeng Lü; Xinhong Zhang; Haijing Dong (PLoS ONE, 2026)
This randomized controlled trial is aimed at evaluating whether external fixation of the urinary catheter to the body surface represents a low-value nursing intervention for patients undergoing transurethral resection of the prostate (TURP). A total of 208 patients who received indwelling urinary catheters after TURP in a tertiary hospital in Qingdao, China between June 2024 and May 2025 were randomly assigned to one of two groups: a nonexternal fixation group (n = 103) and an external body surface fixation group (n = 105). A between-group comparison of outcomes included postoperative hematuria, incidence of catheter-associated urinary tract infection (CAUTI), unplanned catheter removal, occurrence of urinary catheter-related meatal pressure injury (UCR-MPI), and associated economic costs. No significant differences were observed between the two groups in terms of postoperative hematuria or CAUTI incidence (P > 0.05). Unplanned catheter removal did not occur in either group. However, UCR-MPI occurred significantly more frequently in the external fixation group (9 patients) than it did in the nonexternal fixation group (1 patient) (P < 0.05). Additionally, the external fixation group incurred higher costs for personnel and consumables. External fixation of the urinary catheter to the body surface after TURP is associated with increased economic costs, reduced patient comfort, and a higher incidence of UCR-MPI, which indicates that it constitutes a low-value nursing practice. Nonexternal fixation appears to be a safe and effective alternative for post-TURP patients undergoing early mobilization.